(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In-depth study of linguistic languages in foreign languages selected for work in the field of translation is of great importance in the process of linguistic and cultural analysis. It is also necessary to understand and study people’s thinking in the original language in order to understand intercultural differences. Apply lexical, grammatical and methodological methods in accordance with the standards of translation quality improvement. Even the words of color reflect the cultural traditions of different peoples, while the red sign means “danger” in the states, aristocracy in France, life and work in India, anger in Japan, and happiness in China. We can say that the concept of color reflects emotional and emotional factors along with social. The author’s task is to use color expressions in fiction. Rather, it is a tool that reflects the complexities of the language used to develop the author’s creative thinking. In translating literary texts, the translator’s task is to fully convey the author’s intention in the language he is translating. In fiction, colors are also widely used to refer to the protagonist and are based on his or her character. American writer Joif Heller has Captain Black. In the Russian translation of the work (translated by A. Kistyakovsky), the translator calls this man Captain Gnuz, who is embodied in English, emphasizing the negative aspects of the work in terms of darkness, evil, ugliness, ugliness. Gnuz is able to explain the meaning of the original text in Russian.